2016
DOI: 10.1007/jhep07(2016)119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of jet veto resummation on slepton searches

Abstract: Several searches for new physics at the LHC require a fixed number of signal jets, vetoing events with additional jets from QCD radiation. As the probed scale of new physics gets much larger than the jet-veto scale, such jet vetoes strongly impact the QCD perturbative series, causing nontrivial theoretical uncertainties. We consider slepton pair production with 0 signal jets, for which we perform the resummation of jet-veto logarithms and study its impact. Currently, the experimental exclusion limits take the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 154 publications
1
24
0
Order By: Relevance
“…Among the several promising lines of such investigations are those that consider the impact of jet vetoes (i.e., the rejection of events featuring jets with a transverse momentum greater than some threshold p Veto T [15- * Electronic address: fuks@lpthe.jussieu.fr † Electronic address: knordstrom@lpthe.jussieu.fr ‡ Electronic address: richard.ruiz@uclouvain.be § Electronic address: sophie.williamson@kit.edu 19]) in measurements of and searches for heavy, colorless SM [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and beyond the SM [35][36][37][38][39][40][41][42] states. Interestingly, recent studies of multilepton searches for heavy, colorless exotic particles have demonstrated that dynamic jet vetoes can significantly improve discovery potential [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Among the several promising lines of such investigations are those that consider the impact of jet vetoes (i.e., the rejection of events featuring jets with a transverse momentum greater than some threshold p Veto T [15- * Electronic address: fuks@lpthe.jussieu.fr † Electronic address: knordstrom@lpthe.jussieu.fr ‡ Electronic address: richard.ruiz@uclouvain.be § Electronic address: sophie.williamson@kit.edu 19]) in measurements of and searches for heavy, colorless SM [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and beyond the SM [35][36][37][38][39][40][41][42] states. Interestingly, recent studies of multilepton searches for heavy, colorless exotic particles have demonstrated that dynamic jet vetoes can significantly improve discovery potential [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for color-singlet processes occurring at a mass scale Q, vetoes give rise to logarithmic dependencies on p Veto T of the form α s (p Veto T ) log(Q 2 /p Veto 2 necessary to reproduce EW data. Moreover, the effectiveness of vetoes in searches for new high-mass particles is considerably hindered by the higher predisposition of higher mass objects to generate QCD radiation than lighter objects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Following signifiant improvements in modeling soft jet activity in both color-singlet and QCD processes, the use of jet vetoes in direct searches for new phenomena is becoming increasingly standard at the LHC, as shown, for example, in Refs. [47][48][49][95][96][97]. With the TypeI-ISeesaw libraries it is possible to predict jet veto cross sections for triplet scalars up to NLO+NNLL(veto) using the MadGraph5 aMC@NLO-SCET formalism of Refs.…”
Section: Iv11 Triplet Scalar Production With Jet Vetoes At Nlo+nnllmentioning
confidence: 99%